Lip̄nē ‘in the face of’: A Locative Preposition with a Threatening Connotation - Staps, Camil (Journal of Hebrew Scriptures, 2022)
The expression lip̄nē, literally "to the face of," is commonly translated as "before." In combination with the root ngp ("inflict/defeat"), this leads to awkward English translations; e.g., "Israel was defeated before the Philistines" (1 Sam 4:2). What exactly is the role of the Philistines in this event? In recent years, some scholars have used grammaticalization theory to argue that lip̄nē in this context is an Agent marker: "Israel was defeated by the Philistines." However, this view is untenable in the face of arguments from narratology, syntactic-semantic restrictions, grammaticalization theory, and language typology. In present-day English, the near-literal translation "in the face of" is a better alternative: lip̄nē is a simple Locative prepositional expression, but the element "face" has the connotation that Israel is threatened by the Philistines. In other words, Israel is in the "realm of influence" of the Philistines. The actual Agent of ngp is Yahweh, who determines the result of battles, as can be seen in the active voice: "Yahweh defeated Benjamin in the face of Israel" (Judg 20:35). In fact, the meaning of the Hebrew expression is cross-linguistically common; the only problem is that the meaning of the English preposition "before" has shifted, so that the original translation came to be misunderstood.